THE EFFECTIVENESS OF EDUCATIONAL MANAGEMENT IN IMPROVING THE QUALITY OF TEACHERS AND EDUCATIONAL STAFF AT MADRASAH ALIYAH DARUSSYIFA, BUNINAGARA, WEST BANDUNG REGENCY - Rizal Saepuloh; Kosasih Kosasih; Farida Yulianty (Multifinance, 2026)
This study examines the effectiveness of educational management in improving the quality of teachers and educational staff at Madrasah Aliyah Darussyifa, Buninagara, West Bandung Regency, Indonesia. The study employed a quantitative approach using a correlational explanatory design to investigate the extent to which educational management contributes to variations in teacher and educational staff quality. Data were collected from teachers and educational staff through structured questionnaires measuring two main constructs: educational management and personnel quality. The research instrument was assessed for validity and reliability before statistical analysis. Data analysis involved descriptive statistics, normality testing, linear regression analysis, coefficient of determination (R²), t-test, and F-test. The findings indicate that educational management has a positive and statistically significant effect on the quality of teachers and educational staff. Effective management practices, particularly human resource planning, task allocation, professional development, supervision, performance evaluation, and institutional support, contribute to stronger professional competence, work discipline, responsibility, collaboration, and commitment among educational personnel. The regression analysis further indicates that educational management explains a meaningful proportion of the variance in teacher and educational staff quality. These findings highlight the strategic importance of strengthening systematic, transparent, participatory, and continuous educational management to improve the quality of human resources and educational services in madrasahs.